Pengaruh Gerakan Literasi terhadap Minat Baca Peserta Didik di Pkbm An-Nahar - Eko Prasetyo; Abu Sodik; Eco Cahyono; Samsul Maarif (Departement of Mathematics Education, 2023)
Reading is an activity or process of applying the skills of processing reading texts to understand the contents of the reading. Research over the last 20 years found that Indonesia has experienced a decline in the habit of reading books. Likewise, students at PKBM An-Nahar are still very difficult to attend lessons when told to read. Therefore, it is necessary to create a culture of reading so that students' interest in reading increases. One of them is by creating a School Literacy Movement in the PKBM An-Nahar environment. So in this study, the authors wanted to find out how much influence the existence of the school literacy movement had on students' reading interest at PKBM An-Nahar compared to before the literacy movement existed. The method used is descriptive method. Data collection techniques used are observation, interviews, questionnaires. The data analysis technique used is by collecting data, grouping data, processing and analyzing data, and drawing conclusions. Based on the results of the study, students' interest in reading prior to literacy activities was still classified as lacking interest in reading. Meanwhile, after the existence of the literacy movement, students' reading interest increased to sufficient and high. So it can be concluded that the implementation of the Literacy Movement at PKBM An-nahar greatly influences the reading interest of students and other school members.